Barriers to Self-care Among Patients with Heart Failure: A Qualitative Study - Reza Negarandeh (Tabriz University of Medical Sciences, 2021)
Introduction: Heart failure is the most prevalent cardiovascular disease. It is the end stage of most cardiovascular diseases and is characterized by the reduced ability of the heart to pump enough blood to fulfill the metabolic needs of the body. Self-care is the basis of the management of chronic diseases such as heart failure. The aim of this study was to explore the barriers to self-care among patients with heart failure. Methods: This was a qualitative content analysis. Participants were fourteen patients with heart failure and three healthcare providers who were purposively recruited from cardiac care centers in Zanjan, Iran. Data were collected through in-depth semi-structured interviews and were analyzed through the conventional qualitative content analysis approach proposed by Elo and Kyngäs. Results: Self-care barriers -care among patients with HF were categorized into three main categories, namely personal factors, disease burden, and inefficient support system. Each category had three subcategories which were respectively lack of self-care knowledge, heart failure-related negative emotions, the difficulty of changing habits, progressive physical decline, comorbid conditions, financial strain, inadequate social support, healthcare providers’ inattention to self-care, and limited access to healthcare providers. Conclusion: Patients with heart failure face different personal, disease-related, and support-related barriers to self-care. Based on these barriers, healthcare providers can develop interventions for promoting self-care among patients with heart failure.